Synthesis of water-soluble phthalocyanines containing 1-methyl-1H-imidazole-2-thiol: Investigation of DNA nuclease, α-glucosidase inhibitory, and photo-physicochemical properties - Gunsel, Armagan; Kalkan, Fatma; Atmaca, Goknur Yasa; Barut, Burak; Bilgicli, Ahmet T.; Piskin, Hasan; Ozel, Arzu; Erdogmus, Ali; Yarasir, M. Nilufer (WILEY, 2021)
In this work, we have presented on the synthesis and characterization of novel 3-(1-methyl-1H-imidazole-2-thiol)phthalonitrile (1) as a ligand and its nonperipherally (M = 2H (2), Zn(II) (3), and GaCl(III) (4)) phthalocyanines and their highly water-soluble hydrochloride derivatives (2a-4a), containing 1-methyl-1H-imidazole-2-thiol substituents. All compounds were supported by FT-IR, UV-Vis, H-1-NMR, C-13-NMR, and MALDI-TOF mass spectra. The molecular structure of the novel compound (1) and its intermolecular interactions have been elucidated by analyzing the results of X-ray diffraction measurements. In order to determine the supercoiled pBR322 plasmid DNA nuclease properties of compounds (2a-4a), agarose gel electrophoresis was used. The plasmid DNA nuclease did not observe without light irradiation on increasing concentrations (2a-4a). When irradiated at 10 and 20 J/cm(2), the band intensities changed on agarose gel, displaying photonuclease activity on supercoiled pBR322 plasmid DNA of compounds (2a-4a); 4a had the highest photonuclease activities in a concentration-dependent manner at 10 and 20 J/cm(2). The in vitro alpha-glucosidase inhibitory effects of compounds (2a-4a) were investigated to determine whether they can be used in potential agents for diabetes mellitus. Compounds (2a-4a) showed higher inhibitory effects than acarbose (63.03 +/- 2.14 mu M) against alpha-glucosidase enzyme. Lineweaver-Burk analysis showed that K-m increased and V-max remained the same on increasing concentrations of compounds (2a-4a). The finding results claimed that the compounds inhibited alpha-glucosidase enzyme via competitive manner. Dixon plots showed that K-i values of compounds (2a-4a) were 14.70 +/- 0.70, 11.20 +/- 0.50, and 12.60 +/- 0.20 mu M, respectively. Besides, the effect of including metal ion on photochemical and photophysical features of the compounds was studied in DMSO and water, comparatively. The compounds gave high singlet oxygen quantum yields (phi(Delta) = 0.86 for (4a), 0.77 for (3a), and 0.59 for (2a)) in DMSO. The results showed that the compounds are also very suitable for photodynamic therapy applications.
Keywords: crystal structure; DNA cleavage; enzyme inhibition; photochemistry; water‐ soluble phthalocyanine; DISUBSTITUTED SILICON PHTHALOCYANINES; IN-VITRO; ELECTROCHEMICAL PROPERTIES; DERIVATIVES; BINDING; GALLIUM(III); ANTIOXIDANT; KINETICS; Chemistry